2009
DOI: 10.1063/1.3103305
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural evolution of nonpolar (11-20) GaN grown on (1-102) sapphire using a 3D-2D method

Abstract: The microstructure of nonpolar, a-plane (11-20) GaN grown on r-plane (1-102) sapphire, using a three dimensional (3D)-two dimensional (2D) growth transition, has been studied at different stages of metal organic vapor phase epitaxy. The microstructure and morphology of GaN islands formed at the initial stages of growth, as well as the fully coalesced film, were characterized using transmission electron microscopy (TEM) and atomic force microscopy (AFM). The growth of GaN islands (bounded by {10-11} and (000-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 18 publications
2
52
1
Order By: Relevance
“…However, it was found that the defect density is currently much higher in GaN structures grown in such directions [35], unless expensive freestanding non-polar or semi-polar GaN substrates are used [36]. Furthermore, the indium incorporation in the InGaN MQWs grown along non-polar direction is 2-3…”
Section: Internal Electric Fieldmentioning
confidence: 99%
“…However, it was found that the defect density is currently much higher in GaN structures grown in such directions [35], unless expensive freestanding non-polar or semi-polar GaN substrates are used [36]. Furthermore, the indium incorporation in the InGaN MQWs grown along non-polar direction is 2-3…”
Section: Internal Electric Fieldmentioning
confidence: 99%
“…During the second coalescence process, some BSFs are terminated by a formation of either PDs or PSFs, leading to a further reduction in BSF density. 24 Consequently, this forms one area with a low BSF density (i.e., L region) and another area with a high BSF density (i.e., H region), appearing in a periodic form along the m-direction.…”
Section: Aip Advances 6 025201 (2016)mentioning
confidence: 99%
“…TEM measurements have been performed using a Philips EM430 TEM operating at 200 kV. Based on an invisibility criterion, [20][21][22][23][24] dislocations are out of contrast when the product of a diffraction vector g and a dislocation displacement vector R equals zero, namely, g · R=0 (It would still be possible to observe a weak contrast of dislocations for a very thin specimen in the case of the dislocation unparalleled to its burger vector. This does not apply in our case.…”
Section: Aip Advances 6 025201 (2016)mentioning
confidence: 99%
“…Transmission electron microscopy studies on the samples studied here have found that dislocation density decreases with increasing 3D growth time, and the prismatic stacking faults (PSFs) extend through the films at 60° from the GaN/sapphire interface [10]. Hence, the unintentionally-doped features inclined at 60° to the GaN/sapphire interface observed in SCM could be due to enhanced impurity incorporation around PSFs.…”
Section: Discussionmentioning
confidence: 90%